Exploring the Psychological and Spiritual Aspects of Palliative Care Nurses for Cancer Patients in Dharmais Cancer Hospital - Ridlo, Muhamad; Dwi Rahmawati, Agustini Liviana (http://dharmais.co.id/, 2026)
Background: Cancer was a major non-communicable disease that threatened patients’ lives. Nurses had significant responsibilities and roles in palliative care, which created psychological pressures and challenges in service delivery. This study aimed to explore the psychological and spiritual aspects of palliative care nurses for cancer patients in Dharmais Cancer Hospital.Method: The research design used is descriptive qualitative. The sampling technique used was purposive sampling. Study subjects included 15 nurses who performed palliative care for cancer patients and met the inclusion and exclusion criteria that had been made by researchers. Data was collected through semi-structured interviews with face-to-face interviews. There were 13 open-ended questions with an open nature, and an audio recording was done with an average of 40 to 50 minutes. The recordings that have been obtained are verbatim, and interview transcripts are made for analysis. The analysis used the Miles and Huberman method with a thematic analysis approach.Results: The results of the study obtained three themes, among others: a) response to feelings of providing positive care; b) caring for cancer patients; c) sincerity and always getting closer to God.Conclusion: The psychological studies' findings will be a source of information to provide early detection or psychological interventions for nurses in improving mental health while providing palliative care to cancer patients.